2023
DOI: 10.7759/cureus.34867
|View full text |Cite
|
Sign up to set email alerts
|

Behçet’s Disease in Saudi Arabia: Clinical and Demographic Characteristics

Abstract: This study aimed to analyze and determine the clinical features and characteristics of patients diagnosed with Behçet's disease (BD) in Saudi Arabia. MethodsThis single-center study was conducted in a tertiary care center in the western region of Saudi Arabia. Electronic medical records of patients with BD aged 14 years and older were reviewed and their demographic and clinical data were collected by trained rheumatologists. Between comparisons, Fisher's exact test, independent t-test, or Mann-Whitney U test w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In the current research, there were 93.3% males and 6.7% females. These results are consistent with a cohort study in Saudi Arabia where patients were classified as 73.6% males and 26.4% females [11] . Arab populations tend to be predominately male, whereas those of Korea, China, the United States, and even certain northern European nations tend to be predominately female [8] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current research, there were 93.3% males and 6.7% females. These results are consistent with a cohort study in Saudi Arabia where patients were classified as 73.6% males and 26.4% females [11] . Arab populations tend to be predominately male, whereas those of Korea, China, the United States, and even certain northern European nations tend to be predominately female [8] .…”
Section: Discussionsupporting
confidence: 92%
“…This research revealed that 96.7% of studied cases received DMARDS (63.3% on Azathioprine, 26.7% on Cyclosporine, 13.3% on Methotrexate, 3.3% on Leflunomide, 3.3% on cyclophosphamide), 6.7% on adalimumab, 30.0% on infliximab, 90% on steroid, 20% on colchicine and 3.3% on warfarin). While Alharthy et al [11] revealed that patients who received prednisolone were 72.5%, azathioprine was 36.3%, mycophenolate mofetil was 0.75%, cyclosporine was 0.03% and colchicine was 95.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Behçet's symdrome predominantly occurs in populations with historical roots along the Silk Road [4]. Until now, differences in clinical manifestations between males and females with BS have been examined across different geographical regions, such as the Middle East, East Asia, and Europe [6,[11][12][13][14][15]17]. In the Middle East region, one notable multicenter retrospective investigation in Egypt reported a higher prevalence of acne/pseudofolliculitis and vascular involvement in males.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive study involving BS patients from diverse populations revealed significant gender-specific variations, with males exhibiting a notably higher genetic risk score, especially in the human leukocyte antigen (HLA) class I region, compared to female patients [10]. Additionally, observational studies in different geographic regions have underscored gender-associated clinical differences in BS [6,[11][12][13][14][15]. In contrast, some studies from different geographic regions did not find any gender differences in BS [7].…”
Section: Introductionmentioning
confidence: 99%
“…A p-value < 0.05 was considered statistically significant. For our analyses, we used IBM SPSS 29.0 statistical software 35 , which was developed by IBM SPSS Japan, Inc.…”
Section: Discussionmentioning
confidence: 99%